Smart City Strategies for Playas, Ecuador: A Framework for Transformation - Yury Humberto Merizalde email 1; Hernan Vinicio Villa-Sanchez2; Jorge Israel Jaramillo-Ortiz3; Alex David Villao-Villacres4 (Journal of Urban Research, 2025)
General Villamil (Playas), Ecuador, is a well-known tourist destination recognized for its favorable climate and economic accessibility. However, it faces significant challenges in telecommunications, transportation, public services, environmental sustainability, and data-driven decision-making. This article proposes a roadmap to transform Playas into a smart city by leveraging emerging technologies and strategic partnerships, integrating the development of smart infrastructure, implementing IoT-based solutions, big data, artificial intelligence, cloud computing, and cybersecurity, and promoting sustainability through the integration of renewable energy and energy efficiency practices. The methodology is based on a local feasibility analysis, the definition of short-, medium-, and long-term implementation phases, and the establishment of a governance framework that prioritizes citizen participation. The results reveal the need to overcome challenges such as the lack of basic sanitation, limited connectivity, and unequal access to essential services. Additionally, key indicators are proposed to monitor progress, such as reducing energy consumption in public buildings and implementing intelligent waste management systems. Ultimately, adopting these strategies could enhance efficiency, sustainability, and quality of life in Playas, making it a benchmark for other cities undergoing transformation toward smart urban models.